Remaining Engaged: Turkish-US Relations in the Post-Iraq Era - Ker-Lindsay, James (Études helléniques / Hellenic Studies, 2004)
This article explores the American intention to maintain overwhelming global political and military superiority, and take whatever action is needed to preserve the 'new world order' and prevent the emergence of a rival power. Superpower status is by no means confined to the milirary dimension, as the US still has the largest and most vibrant single national economy. In the near future, no other country or combination of countries can hope to challenge American prominence. At the same time, however, as the 9/11 attacks demonstrated, the US is structurally vulnerable and the cost of its global engagement greater than many Americans thought.